Recruiting community health centers into pragmatic research: Findings from STOP CRC. (April 2016) - Coronado, Gloria D; Retecki, Sally; Schneider, Jennifer; Taplin, Stephen H; Burdick, Tim; Green, Beverly B
Background: Challenges of recruiting participants into pragmatic trials, particularly at the level of the health system, remain largely unexplored. As part of Strategies and Opportunities to STOP Colon Cancer in Priority Populations (STOP CRC), we recruited eight separate community health centers (consisting of 26 individual safety net clinics) into a large comparative effectiveness pragmatic study to evaluate methods of raising the rates of colorectal cancer screening. Methods: In partnership with STOP CRC's advisory board, we defined criteria to identify eligible health centers and applied these criteria to a list of health centers in Washington, Oregon, and California affiliated with Oregon Community Health Information Network, a 16-state practice-based research network of federally sponsored health centers. Project staff contacted centers that met eligibility criteria and arranged in-person meetings of key study investigators with health center leadership teams. We used the Consolidated Framework for Implementation Research to thematically analyze the content of discussions during these meetings to identify major facilitators of and barriers to health center participation. Results: From an initial list of 41 health centers, 11 met the initial inclusion criteria. Of these, leaders at three centers declined and at eight centers (26 clinic sites) agreed to participate (73%). Participating and nonparticipating health centers were similar with respect to clinic size, percent Hispanic patients, and percent uninsured patients. Participating health centers had higher proportions of Medicaid patients and higher baseline colorectal cancer screening rates. Common facilitators of participation were perception by center leadership that the project was an opportunity to increase colorectal cancer screening rates and to use electronic health record tools for population management. Barriers to participation were concerns of center leaders about ability to provide fecal testing to and assure follow-up of uninsured patients, limited clinic capacity to prepare mailings required by the study protocol, discomfort with randomization, and concerns about delaying program implementation at some clinics due to the research requirements. Conclusion: Our findings address an important research gap and may inform future efforts to recruit community health centers into pragmatic research.